Monomeric C-reactive protein is associated with severity and prognosis of decompensated hepatitis B cirrhosis - Gao, Ning; Yuan, Ping; Tang, Zhao-Ming; Lei, Jia-Geng; Yang, Ze-Rui; Ahmed, Mustafa; Yao, Zhen-Yu; Liang, Dan; Wu, Yi; Li, Hai-Yun (Frontiers in Immunology, 2024)
C-reactive protein (CRP) is an acute-phase protein produced by the liver in response to infection and during chronic inflammatory disorders. Systemic inflammation is a major driver of cirrhosis progression from the compensated to the decompensated stage.Previous studies have shown that pentameric CRP (pCRP) to be a weak predictor of disease severity and prognosis in patients with decompensated hepatitis B cirrhosis, with it being only helpful for identifying patients with a higher short-term risk of death under certain conditions. Accumulating evidence indicates that pCRP dissociates to and acts primarily as the monomeric conformation (mCRP) at inflammatory loci, suggesting that mCRP may be a potentially superior disease marker with higher specificity and relevance to pathogenesis. However, it is unknown whether mCRP and anti-mCRP autoantibodies are associated with disease severity, or progression in decompensated hepatitis B cirrhosis. In this study, we evaluated the serum levels of mCRP and anti-mCRP autoantibodies in patients with decompensated cirrhosis of hepatitis B and their association with disease severity and theoretical prognosis. The results showed that patients with high mCRP and anti-mCRP autoantibody levels had more severe liver damage and that coagulation function was worse in patients with high anti-mCRP autoantibodies. Analysis of the correlation between pCRP, mCRP and anti-mCRP autoantibody levels with Model for End-Stage Liver Disease (MELD), Albumin-Bilirubin (ALBI), and Child-Turcotte-Pugh (CTP) prognostic scores showed that mCRP was the most strongly correlated with MELD score, followed by anti-mCRP autoantibodies; conversely, pCRP was not significantly correlated with prognostic score. Therefore, mCRP and anti-mCRP autoantibodies may be more advantageous clinical indicators than pCRP for evaluating the pathological state of decompensated hepatitis B cirrhosis.